Agreement of Serum Spec cPL with the 1, 2‐o‐Dilauryl‐Rac‐Glycero Glutaric Acid‐(6′‐methylresorufin) Ester (DGGR) Lipase Assay and with Pancreatic Ultrasonography in Dogs with Suspected Pancreatitis. (5th March 2014) - Kook, P.H.; Kohler, N.; Hartnack, S.; Riond, B.; Reusch, C.E.
<x xml:space="preserve">Abstract</x> Background Spec cPL is the most sensitive and specific test for diagnosing pancreatitis in dogs. Its results have not been compared to those of the 1, 2‐o‐dilauryl‐rac‐glycero‐3‐glutaric acid‐(6′‐methylresorufin) ester (DGGR) lipase assay or those of abdominal ultrasonography. Objectives To investigate agreement of Spec cPL with DGGR lipase activity and pancreatic ultrasonography in dogs with suspected pancreatitis. Animals One hundred and forty‐two dogs. Methods DGGR lipase activity (reference range, 24–108 U/L) and Spec cPL were measured using the same sample. The time interval between ultrasonography and lipase determinations was <24 hours. The agreement of the 2 lipase assays at different cutoffs and the agreement between pancreatic ultrasonography and the 2 tests were assessed using Cohen's kappa coefficient (κ). Results DGGR lipase (>108, >216 U/L) and Spec cPL (>200 μg/L) had κ values of 0.79 (95% confidence interval [CI], 0.69–0.9) and 0.70 (CI, 0.58–0.82). DGGR lipase (>108, >216 U/L) and Spec cPL (>400 μg/L) had κ values of 0.55 (CI, 0.43–0.67) and κ of 0.80 (CI, 0.71–0.9). An ultrasonographic diagnosis of pancreatitis and DGGR lipase (>108, >216 U/L) had κ values of 0.29 (CI, 0.14–0.44) and 0.35 (CI, 0.18–0.52). Ultrasonographically diagnosed pancreatitis and Spec cPL (>200, >400 μg/L) had κ values of 0.25 (CI, 0.08–0.41) and 0.27 (CI, 0.09–0.45). Conclusions and Clinical Importance Although both lipase assays showed high agreement, agreement between ultrasonography and lipase assays results was only fair. Because lipase results are deemed more accurate, ultrasonography results should be interpreted carefully.